PERILAKU EKONOMI PARA PIHAK DALAM PEMANFAATAN TUMBUHAN OBAT DI TN MERU BETIRI JAWA TIMUR - Ignatius Adi Nugroho; Dodik Ridho Nurrochmat; Hardjanto Hardjanto; Latifah Kosim Kadarusman; Agus Poerwadianto (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2016)
The economic behavior of  stakeholders in Meru Betiri National Park (MBNP) are determined by their access in utilizing the  medicinal plants.  The access i.e: technology, capital, market, labor, knowledge, authority, social identity and negotiation by social relation are needed in utilizing those products.  The benefits, transaction cost and natural insurance are economic factors that follow the stakeholder's behavior in MBNP.  This study aims to analyze socio and economic behavior of  rural community near the MBNP by identifying their access variabels, benefit cost ratio, transaction cost and natural insurance. The results showed that the stakeholders hadthree access variables to utilizatio n of  medicinal plants in MBNP i.e. access to the technology, capital and market.  Based on statistical analysis, only access to the market that had positive value while others were negative, this indicates that stakeholder's behavior depend on the single buyer of  medicinal plant products, and need empowerment in technology and capital. The stakeholder had a tendency to behave like seller than buyer. Most of  the stakeholders gained benefit from extraction of  the medicinal plant products, but the benefits had to be shared with other persons who had same interest on  the medicinal plants product through trading.